Joint replenishment of zinc and folic acid enhances the anti-depressive effect of paroxetine via increasing serum calcium and copper and decreasing serum arsenic. (15th October 2020) - Gong, Anjing; Wan, Dehong; Liang, Hui; Yan, Liping; Yu, Zhou; Zhang, Huizhen; Wang, Qiuzhen; Dou, Mei
Graphical abstract: Highlights: Supplementation of zinc and folacin improved behavior responses to paroxetine. The supplementation increased the serum level of calcium and copper. The supplementation reduced the serum level of arsenic. The changes of these elements may contribute to the behavior benefit of the supplementation. Abstract: Insufficient zinc and folic acid levels are associated with depression and poor response to antidepressants. This study aimed to investigate the influences of combined zinc and folic acid replenishment on the anti-depressive effect of paroxetine. Male rats were randomly divided into five groups: control (C), model (M), paroxetine (MP), zinc + folic acid (MZnF), and zinc + folic acid + paroxetine (MZnFP) groups. Rats were exposed to mild unpredictable stress for 3 weeks as a depression model. The combinations of drug and supplements were applied via daily gavage for 4 weeks. The open field test was conducted to observe behavioral changes. A chemiluminescence method was used to detect folacin, and inductively coupled plasma mass spectrometry was used to detect serum elements. Supplementation of zinc and folic acid significantly improved behavior responses to paroxetine, including movement speed, total distance, and central zone frequency. In addition, higher calcium and copper levels and a lower arsenic level were found in the serum of the MZnFP group. Thus, supplementation of zinc and folacin can enhance the anti-depressive effect of paroxetine, and the mechanism is potentially related to the improved levels of calcium and copper and a reduced level of arsenic.